Upaya Hukum PT Bank Rakyat Indonesia (Persero) Tbk Unit Amlapura terhadap Debitur yang Wanprestasi dalam Usaha Mikro - I Kadek Adi Payana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
Economic development in a country is highly dependent on dynamic development and tangible contributions from the development sector. Development in the economic field is the main driver of development, Micro Business plays an important role in development and economic growth, not only in developing countries but also in developed countries. The formulation of the problem in this study, is: 1. Default and Legal Consequences in Micro People's Business Credit Agreement at PT. Bank BRI, 2. Repayment of Debtor Debt in Credit Agreements at Bank Bri. The research method used is a type of normative legal research. The most important part of developing a micro business is borrowing venture capital obtained from loans obtained from a bank. In an agreement, the debtor sometimes fails or defaults. Default or non-fulfillment of the agreement can occur either intentionally or unintentionally. Parties who do not intentionally do this default can occur because they are not able to fulfill these achievements or are also forced to make these achievements. The problem in this study is the occurrence of default on a credit agreement, the data is processed and analyzed qualitatively. The purpose of the analysis is to minimize the risk of bad credit. Then sort out the loan application submitted based on the loan ceiling. Default or non-fulfillment of the agreement can occur either intentionally or unintentionally. Parties who do not intentionally do this default can occur because they are not able to fulfill these achievements or are also forced to make these achievements.